Pengembangan LKS Tabela Berbasis Bahan Praktikum Lokal untuk Meningkatkan Keterampilan Proses Sains Siswa SD - Rita Rahmaniati; Misyanto Misyanto; Agung Riadin (Anterior Jurnal, 2018)
The study aimed to Produce Tabela worksheets based on standard local practicum materials, Find out the increase and influence of science process skills, and describe the students' responses after learning using Tabela worksheets. The method of the research was Research & Development with the ADDIE model. The first stage analyzed the needs of the Tabela worksheets based on local practicum materials. The second stage carried out the development of the Tabela worksheets based on local practicum materials using the ADDIE Model. The third stage carried out Implementation/testing on the level of effectiveness, efficiency, and product attractiveness toward the developed product using a quasi-experimental design with a design. The results of product showed that Tabela worksheets had good attractiveness criteria with the score of 3.31, good of efficiency criteria with a score of 3.33, and very good of effectiveness criteria with a score of 3.60. The development result of Tabela worksheets by expert test results stated feasible to use as instructional materials / learning media. And it was shown in the significance test that is the influence of Tabela worksheet on learning outcomes of the tcount> ttable (7.442> 1.668). The effectiveness test showed that there was no significant difference and indicated by tcount> ttable (1.615 <1.673), but the student learning outcomes increased with the average pretest of 43.44 and posttest of 61.09. The differences between pretest and posttest in the average score were 17.65 and N gain was 0.31 in the medium category. The students provided positive responses using Tabela worksheets.